UPAYA INTERNATIONAL SOCIETY OF AESTHETIC PLASTIC SURGERY (ISAPS) DALAM MEMPROMOSIKAN OPERASI PLASTIK DI KOREA SELATAN - Dara Yuliyanti Ningsih; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to find out about The International Society of Aesthetic Plastic Surgery (ISAPS) efforts to promoting aesthetic plastic surgery in South Korea. Compared to other countries, South Korea has the highest desire to achieve the ideal appearance. It is estimated that at least 1 out of 5 woman in South Korea have plastic surgery. According to data of the International Society of Aesthetic Plastic Surgery (ISAPS) also shows that South Korea as the country has the highest per capita level of expenditure in the world in terms of plastic surgery.The data used in this study a secondary data. Secondary data was obtained through library research, and search online media research. The writer uses of the pluralism prespective, and organization level of analysis. Theories used in this study based on the role of international organization theory by Clive Archer.The research result is the effort of International Society of Aesthetic Plastic Surgery (ISAPS) to promoting plastic surgery in South Korea through a branding, “A Commitment to Safer Aesthetic Plastic Surgery Worldwide”, realization of that is ISAPS do Surgeon qualifications, Surgeon training, Facility accreditation, Patient education, Consumer protection, and create ISAPS Global Alliance Participating Societies.Keywords: International Society of Aesthetic Plastic Surgery (ISAPS), effort, aesthetic plastic surgery, patient safety